Hubungan Senam Hamil pada Ibu Hamil Trimester 3 dengan Kelancaran Proses Persalinan di Wilayah Kerja Puskesmas Rawat Inap Malingping - Tiara Nurfadilla Putri; Omega DR Tahun (Malahayati Nursing Journal, 2024)
ABSTRACT Pregnancy exercise is a method that can facilitate the delivery process and get relaxation for pregnancy, Exercise during pregnancy aims to provide readiness and train the muscles to function optimally during the delivery process (Varney in Semangga Fausyah, 2021). In Malingping District, mothers with pregnancy disorders experienced during childbirth will number 8 in 2022, 20 in 2021, and 22 in 2020. The Malingping Inpatient Health Center organizes a Pregnant women's Exercise class program to provide education and understanding in order to make it easier for pregnant women and provide smoothness in carrying out the delivery process later. Knowing the relationship between Pregnancy Exercise for 3rd trimester Pregnant Women and the Smooth Delivery Process in the working area of the Malingping Inpatient Health Center in 2023. This research is quantitative with analytic correlation. The use of the purposive sampling technique with a total of 44 respondents participating in the Pregnant Women's Class program This study uses the Pregnancy Exercise variable as the independent variable and the Smooth Delivery Process variable as the dependent variable. The data used were medical records that were recorded at the Malingping Inpatient Health Center, which were then analyzed through Univariate analysis and Bivariate analysis using the Chi-Square Test in the SPSS program. Result of the 44 respondents, 31 (70.5%) routinely carried out pregnancy exercise activities and had a smooth delivery process. And based on the results of the Chi-Square Test, the sig.p. Value is 0.001, where the value is 0.05. There is a significant relationship between Pregnancy Exercise in the 3rd trimester and the smooth delivery process in the working area of the Malingping Inpatient Health Center in 2023. Keywords: Pregnancy Exercise, Smooth Delivery Process, 3rd Trimester Pregnant Women  ABSTRAK Senam Hamil merupakan salah satu metode yang dapat memudahkan proses persalinan dan mendapatkan relaksasi terhadap kehamilan, dimana senam pada masa kehamilan bertujuan agar memberikan kesiapan dan melatih otot agar berfungsi optiman pada saat proses persalinan (Varney dalam Semangga Fausyah, 2021). Di Kecamatan Malingping, jumlah ibu dengan gangguan kehamilan yang dialami pada saat bersalin sebanyak 8 orang pada tahun 2022, 20 orang pada tahun 2021, dan 22 orang pada tahun 2020. Puskesmas Rawat Inap Malingping menyelenggarakan program kelas Senam Ibu Hamil guna memberikan edukasi dan pemahaman agar mempermudah Ibu Hamil dan memberikan kelancaran dalam melaksanakan proses persalinan nantinya. Mengetahui hubungan antara Senam Hamil pada Ibu Hamil trimester 3 dengan Kelancaran Proses Persalinan di wilayah kerja Puskesmas Rawat Inap Malingping tahun 2023. Penelitian berjenis kuantitatif yang bersifat analitik korelasi. Penggunaan teknik Purposive Sampling dengan jumlah sebanyak 44 responden peserta Ibu Hamil dalam program Kelas Ibu Hamil. Penelitian ini menggunakan variabel Senam Hamil sebagai variabel independen dan variabel Proses Persalinan sebagai variabel dependen. Data yang digunakan merupakan rekam medik yang tercatat di Puskesmas Rawat Inap Malingping yang kemudian dianalisis melalui analisis Univariat dan analisis Bivariat dengan menggunakan Uji Chi-Square pada program SPSS. Dari total 44 orang responden, 31 orang (70,5%) diantaranya rutin melakukan kegiatan senam hamil dan menjalani proses persalinan dengan lancar. Dan berdasarkan hasil Uji Chi-Square, didapat Nilai Sig.p Value = 0,000, dimana nilai tersebut 0,05. Adanya Hubungan antara Senam Ibu Hamil pada Ibu Hamil trimester 3 dengan kelancaran proses persalinan di wilayah kerja Puskesmas Rawat Inap Malingping tahun 2023. Kata Kunci: Senam Hamil, Kelancaran Proses Persalinan, Ibu Hamil Trimester 3